2020
DOI: 10.1289/ehp6803
|View full text |Cite
|
Sign up to set email alerts
|

Associations of a Metal Mixture Measured in Multiple Biomarkers with IQ: Evidence from Italian Adolescents Living near Ferroalloy Industry

Abstract: BACKGROUND: Research on the health effects of chemical mixtures has focused mainly on early life rather than adolescence, a potentially important developmental life stage. OBJECTIVES: We examined associations of a metal mixture with general cognition in a cross-sectional study of adolescents residing near ferromanganese industry, a source of airborne metals emissions. METHODS: We measured manganese (Mn), lead (Pb), copper (Cu), and chromium (Cr) in hair, blood, urine, nails, and saliva from 635 Italian adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 88 publications
0
36
0
Order By: Relevance
“…Indeed, in our study, Zn showed the largest increase, being almost doubled after exercise. Zn together with other metals like Se and Mn is one of the essential elements usually measured to monitor nutritional status; however, also these metals are present in polluted air, and when their concentration is excessively high, being emitted by coal and wood combustions, industrial fossil powers, welding processes, steel mills, waste incinerators, traffic pollution, etc., they can indeed cause disease (Bauer et al 2020 ; Chowdhury et al 2018 ; Kieliszek 2021 ; Knoop et al 2020 ; Montano et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in our study, Zn showed the largest increase, being almost doubled after exercise. Zn together with other metals like Se and Mn is one of the essential elements usually measured to monitor nutritional status; however, also these metals are present in polluted air, and when their concentration is excessively high, being emitted by coal and wood combustions, industrial fossil powers, welding processes, steel mills, waste incinerators, traffic pollution, etc., they can indeed cause disease (Bauer et al 2020 ; Chowdhury et al 2018 ; Kieliszek 2021 ; Knoop et al 2020 ; Montano et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that environmental chronic metals exposure in non-occupationally exposed general population is associated with several pathologic conditions including an increased risk of all-cause, cancer, and cardiovascular disease mortality (Chowdhury et al 2018 ; Men et al 2020 ; Menke et al 2009 ; Newby et al 2015 ). Environmental exposure to metals can have even neurotoxic effects; notably, Cr, Mn, and Pb were associated with lower Intellectual Quotient scores (Bauer et al 2020 ; Lucchini et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two limitations in using cord blood Mn as a biomarker of Mn exposure include a lack of consensus about which biological matrix is the most valid biomarker of prenatal Mn exposure and using ICP-MS to detect cord blood Mn as the Mn isotope has a similar mass to two isotopes of iron which may result in iron contributing to the Mn signal among those with high iron levels [58]. However, there is evidence that cord blood Mn correlates well with third-trimester tooth Mn and is, therefore, a valid biomarker of prenatal Mn exposure [59][60][61] and adequate separation of Mn and iron occurred in the laboratory in which these analyses took place.…”
Section: Discussionmentioning
confidence: 99%
“…The inhalation route of exposure is particularly important for people living close to airborne metal(loid)s emission sources in urban and industrial areas (Bauer et al, 2020 ), such as metallurgy, steelworks, combustion (including transportation) and incineration. Airborne metal(loid)s are bound to particulate matter (PM), its particle size being a key parameter on the fate of such pollutants in the human body (Kelly & Fussell, 2012 ).…”
Section: Introductionmentioning
confidence: 99%